Excitation of afferent cardiac sympathetic nerve fibres during myocardial ischaemia - Brown, A. M. (1967)
1. Occlusion of the main left coronary artery of lightly anaesthetized cats provoked a pseudaffective reaction. The afferent pathway was in the cardiac sympathetic nerves. 2. The compound action potential evoked in the inferior or middle cardiac nerves by stimulation of the thoracic sympathetic trunk contained two elevations, a small Aδ wave and a much larger sC wave. Occasionally a B wave was present. 3. During coronary occlusion, the Aδ elevation was reduced by 35-55%, indicating afferent activity in these fibres. Multifibre preparations also showed increased afferent discharge during occlusion. 4. It seems probable that the afferent activity in these fibres was mainly responsible for signalling the pseudaffective response elicited by coronary occlusion. 5. Myocardial ischaemia produced by coronary occlusion was probably the stimulus for the increased activity.